Ragnarok Online, Reality of Virtual Phenomenon - Alvanov Zpalanzani Mansoor; Hafiz Aziz Ahmad (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2009)
Originated from South Korea, Ragnarok Online is an entertainment product in comics and games which is popular in the world especially South-East Asia. Ragnarok in Nordic Mythology described as the doom of the gods. In the case above, Ragnarok is used as a background setting of a comic, which created, by Lee Myung Jin and Ragnarok MMORPG based on that comic. Internet is described as a many-to-many medium. Games turn out to be one of the first popular settles in the Internet among e-commerce, portals, free advertisers, and sexual exploitation sites. Online Game becomes a new frontier that could connect people to interact and play similar game on the same time and Massive Multiplayer Online Role Playing Game of Ragnarok is one of the best and successful Online Game worldwide. It is one of the phenomena in online gaming today. Recently, official Ragnarok Online Characters (NPC, Monsters and Players Characters) have developed in quantity approximately 200 and still have possibility to increase. In international Ragnarok Online provider, more than 120,000 customers connected in 12 servers on real time basis at the same time everyday and this exclude local Ragnarok Server provided by several countries with similar number of player.Ragnarok Online is a virtual representation of reality, it creates and represents visual social semiotics, which became very important element of communication in recent years. As one of visual product in modern culture, the distance between reality and virtual realm become closer and sometimes it blurred and formed new realm. A new dawn of community born in virtual realm and develop in some way that many though it would consume the community it represented. Is it possible that the characters and environmental design, which is built, really has the enormous attraction? Or is there something else work behind the surface such as the representation and online culture. Although there are many contradictions about the impacts of Ragnarok Online, this paper is endeavors a new insight of Ragnarok Online, which may have not being researched by others. The combination of online culture and virtual media design with interactive and inviting visual interface may open wide the possibilty of encountering new methods and keys of success in designing digital media through descriptive analysis.